Análise clínico-epidemiológica de casos de ofidismo atendidos em um hospital público estadual de Minas Gerais de 2003 a 2012 - Adebal de Andrade Filho (2015)
A descriptive and retrospective study was conducted to assess clinical and epidemiological characteristics of snakebite patients assisted from 2003 to 2012 at Hospital João XXIII (HJXXIII) in Belo Horizonte, Minas Gerais. Data were collected concerning victims' demographics, snakebites characteristics, clinical manifestations, severity rating according to both the classification criteria adopted by the Ministry of Health of Brazil and the Manchester Protocol, antivenom use and outcomes. 834 cases, treated over ten years at HJXXIII, were analyzed. Approximately half of the accidents were caused by non-venomous snakes. Around 75% of patients were male and 51% were aged between 20 and 49 years. Most of the accidents occurred in the summer and during the day, with a higher concentration at the end of the afternoon and in the early evening. Accidents involving non-venomous animals were more frequent in the state capital, and those involving venomous ones were more frequent in smaller towns within the state of Minas Gerais. Rattlesnakes accounted for 52% of the venomous snake accidents. The anatomical regions most affected by bites (around 80%) were below the knee. There was no observed association between the severity of the injury and the affected body region. Before admission to hospital, some form of amateur treatment was performed on less than 6% of the patients. The clinical picture created by each of the three genres studied are in accordance with current literature. The neurotoxic manifestations were more frequent in crotalic and elapid accidents, hemorrhagic in bothropic and rhabdomyolysis in crotalic ones. On admission, 54% of the cases were classified as moderate, 26% as severe and 20% as mild. In 65 of the cases (16.6%) there was a need for additional snakebite serum, due to initial underestimation of the severity. Approximately 15% of the crotalic cases, and 22% of the bothropic, reached the HJXXIII more than seven hours after the accident. The median length of stay in the emergency department for victims of non-venomous snake bites was 4.8 hours, while that for those bitten by venomous snakes was 2.9 days. Only 7% of victims bitten by venomous snakes required admission to intensive care. Of those patients who received snakebite serum, 4.4% also received drugs to prevent a hypersensitivity reaction. Of these, 25% had an allergic reaction. In the group that did not receive pre-antivenom medication, the incidence was 42.7%. However, there is no statistically significant difference between these results. Most hypersensitivity reactions were classified as mild or moderate, predominantly cutaneous manifestations. The patients ages were not related to a higher incidence of immediate hypersensitivity reactions. Some factors had a direct correlation with a greater severity of snakebite: ages below 10 or above 60 years, and a time of arrival at hospital greater than five hours after the accident. The mortality rate was 0.48%, permanent disability 0.1% and temporary disability 2.4%.